SHLA-G and sHLA-I levels in follicular fluid are not associated with successful implantation. (February 2016) - Ouji-Sageshima, Noriko; Yuui, Katsuya; Nakanishi, Mari; Takeda, Nobuyoshi; Odawara, Yasushi; Yamashita, Masanori; Iwayama, Hiroshi; Awai, Keiko; Hashimoto, Hirotsugu; Geraghty, Daniel E.; Ishitani, Akiko; Hatake, Katsuhiko; et al.
Highlights: We examined the variation in sHLA-G levels among multiple FFs from one patient. The variation in sHLA-G levels was not related to successful implantation. The difference in sHLA-G levels was not related to successful implantation. We tested the presence of sHLA-G using immunoprecipitation (IP) and western blot (WB). The measurement of sHLA-G in FFs was not meaningful for selecting good oocytes. Abstract: In the field of in vitro fertilization (IVF), useful markers for the prediction of successful implantation for oocyte or embryo selection are essential. It has been reported that sHLA-G (sHLA-G1/HLA-G5) could be detected in the supernatant of the fertilized embryo and in follicular fluid samples (FFs), and that the presence of sHLA-G was related to successful implantation. If sHLA-G could be used as a marker of oocyte selection from multiple FFs, oocytes could be selected without physical contact, thus reducing the likelihood of damage. To investigate the potential for sHLA-G as a marker of oocyte selection from multiple FFs in one patient, protein levels of total protein, sHLA-G, and sHLA-I (sHLA-A, B, and C) were examined in FFs. The variation among multiple FFs in total protein level and sHLA-G level was not related to successful pregnancy. The average sHLA-I levels did not differ in the successful implantation and unsuccessful implantation groups, indicating that sHLA-I levels were not related to successful pregnancy. Furthermore, sHLA-G in FFs was not detected by western blotting, despite being detected by ELISA, while sHLA-I was detected by both ELISA and western blot. These data suggest that sHLA-G in FF might not be a useful marker for oocyte selection as measurements of sHLA-G were inconsistent and there was no association with successful pregnancy. Further, more rigorously tested ELISA systems for detecting sHLA-G in body fluids are necessary before the utility of sHLA-G for diagnosis can be established.